Environmental Conflicts and Regional Conflict Resolution - Chukwunedum, Ogochukwu Chinedum; Godspower Onyekachukwu Ekwueme; Anizoba, Daniel Chinazom (Sean Institute, 2025)
This article examines when and how environmental scarcity and degradation lead to conflicts, and how countries resolve conflicts over the sharing of renewable resources between different states. Two research programs related to environmentally-based conflicts are reviewed, and about thirty activities for resolving environmental conflicts are listed. A single example of the Nile Basin Initiative is dealt with in particular detail. Three main conclusions can be drawn: First, scarcity of renewable resources and environmental degradation can lead to conflict when they interfere with each other under certain political and socio-economic conditions. Such conflicts can become serious in the internal settlement process, often in the context of political instability and poverty. International environmental conflicts, however, very rarely lead to military action. Yet the lack of international cooperation when sharing resources, based on the interests of various states, it really prevents the adequate development of these resources, thereby leading to overuse or underutilization of the resource, or to obvious “natural” disasters such as droughts and floods. These negative consequences, in turn, can collectively lead to poverty, migration and conflict. Second, there are indications that the assistance of a third party, usually an International Government Organization (IGO), is often more effective in reducing international tensions and enhancing environmental sustainability than conflicts governed solely by the conflicting parties themselves. Moreover, examples further demonstrate that conflict resolution efforts are likely to be more successful when they place a strong emphasis on common interests, focus on efficiency and require external resolution, and when they are jointly involved in sharing costs and revenues. Third, the above examples of conflict resolution show that International Governmental Organizations should strengthen their role as mediators from an independent third party. IGOs must support the participants without taking responsibility for the process itself or the results. A “cross-cutting” settlement, that is, measures to link the government with middle and lower-level leaders, is necessary to avoid shifting the problem from the international arena to the national level.